THE AUTHORITY OF THE UNITED NATIONS SECURITY COUNCIL IN MAINTAINING INTERNATIONAL PEACE AND SECURITY: A SYSTEMATIC LITERATURE REVIEW ANALYSIS OF ARTICLES 24-25 OF THE UN CHARTER, MEMBER STATES' COMPLIANCE OBLIGATIONS, AND THE LEGAL IMPLICATIONS OF RESOLUTIONS ON GLOBAL THREATS AND THE ENFORCEMENT OF INTERNATIONAL LAW - Era Purike (Adisam Publisher, 2026)
This study analyses the binding authority of the UN Security Council in maintaining international peace and security through a systematic literature review of Articles 24–25 of the UN Charter, the obligations of member states, and the legal implications of resolutions on global threats. The findings confirm that Chapter VII resolutions are legally binding under Article 25, requiring states to implement sanctions, adjust national laws, and cooperate in dealing with terrorism (Resolution 1373), nuclear proliferation (Resolution 1718/2397), and the establishment of ad hoc tribunals. Although effective in the evolution of jus cogens norms, the challenges of veto politicisation and compliance gaps undermine the legitimacy of international law enforcement